1α-Hydroxycholecalciferol improves the growth performance and up-regulates the mRNA expression of vitamin D receptor in the small intestine and kidney of broiler chickens. (14th March 2018) - Han, J C; Wang, J G; Chen, G H; Zhang, J L; Zhang, N; Qu, H X; Guo, Y; Yan, Y F; Yang, X J
Abstract: 1α-Hydroxycholecalciferol (1α-OH-D3 ) is a vitamin D derivative. The objective of this study was to evaluate the effects of 1α-OH-D3 on the growth and the mRNA expression of vitamin D receptor (VDR) in the small intestine and kidney of chickens. A total of 240 males of one-day-old Ross 308 broilers was randomly assigned to 4 treatments with 5 replicates of 12 birds per replicate. Three levels of 1α-OH-D3 (1.25, 2.5, and 5 μg/kg) were added to a basal diet containing 0.50% calcium (Ca), 0.25% non-phytate phosphorus (NPP), and without supplemental cholecalciferol (vitamin D3 ). The control diet contained 1.00% Ca, 0.45% NPP, and 25 μg/kg cholecalciferol. Dietary 1α-OH-D3 levels linearly improved the average daily feed intake (ADFI), average daily gain (ADG), femur and tibia mineralization, and plasma Ca concentration, and retained Ca and total phosphorus (tP) amounts in broilers from 1 to 21 d of age ( P < 0.05). In addition, 1α-OH-D3 also linearly up-regulated the mRNA expression levels of VDR in the duodenum as well as those of VDR and sodium-phosphate cotransporter NaPi-IIa and NaPi-IIc in the kidney of broilers ( P < 0.05). However, 1α-OH-D3 did not affect the mRNA levels of 25-hydroxylase in the liver or NaPi-IIb in the duodenum ( P > 0.05). No differences were observed in the ADFI, ADG, bone length, plasma mineral concentration, retained tP amount, or the mRNA levels of the above genes (except for VDR in the kidney) between the birds fed the diet with 5 μg/kg 1α-OH-D3 and the birds fed the control diet ( P > 0.05). By contrast, the weight, ash weight, ash percentage, and Ca percentage of the bone, retained Ca amount, and the mRNA level of VDR in the kidney were lower in the birds fed the diet with 5 μg/kg 1α-OH-D3 than in the birds fed the control diet ( P < 0.05). These data indicate that 1α-OH-D3 up-regulates the gene expression of VDR in the small intestine and kidney at the transcriptional level, thereby improving the growth performance and bone mineralization of broiler chickens from 1 to 21 d of age.